2020
DOI: 10.22271/chemi.2020.v8.i4f.9723
|View full text |Cite
|
Sign up to set email alerts
|

Weed management in direct seeded rice: A review

Abstract: Direct seeding is done by sowing of pre-germinated rice seeds under puddled condition either manually or by drum seeding methods. Direct seeded rice (DSR) cultivation needs only 34 per cent of the total labour requirement and saves 29 per cent of the total cost of the transplanted rice. Weed infestation and competition are severe in direct wet seeded rice as compared to transplanted rice, because of the simultaneous growth of both crops and weeds. Uncontrolled weeds decreased the yield by 96 per cent in dry DS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 25 publications
7
14
0
Order By: Relevance
“…PE herbicide along with EPOE herbicide effectively reduced the weed biomass. This is in agreement with the findings of Bhagat Singh et al (2009) and Rathika and Ramesh (2019) who reported that weeds in DSR could be kept at lower level by herbicides.…”
Section: Weed Control Efficiencysupporting
confidence: 93%
See 4 more Smart Citations
“…PE herbicide along with EPOE herbicide effectively reduced the weed biomass. This is in agreement with the findings of Bhagat Singh et al (2009) and Rathika and Ramesh (2019) who reported that weeds in DSR could be kept at lower level by herbicides.…”
Section: Weed Control Efficiencysupporting
confidence: 93%
“…Effective control of weeds in these treatments might be due to application of two herbicides in sequence could be more useful have resulted in decreased weed seed reserve in the soil. This is in line with the findings of Ajay Singh et al (2017) and Rathika and Ramesh (2019).…”
Section: Total Weed Density and Dry Weightsupporting
confidence: 93%
See 3 more Smart Citations